2023
DOI: 10.1108/apjba-05-2022-0216
|View full text |Cite
|
Sign up to set email alerts
|

The greenwashing effects on corporate reputation and brand hate, through environmental performance and green perceived risk

Abstract: PurposeWhen a company practices greenwashing, it violates consumers' expectations by deliberately deceiving them about their environmental practices or the benefits of their products/services. This study investigated the effects of greenwashing on corporate reputation and brand hate. Furthermore, this study explored the mediating effects of perceived environmental performance and green perceived risk.Design/methodology/approachA survey design using cross-sectional primary data from 420 Portuguese consumers who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 103 publications
1
3
0
Order By: Relevance
“…Second, this study addressed the fact that greenwashing has a detrimental impact on brand reputation. This result is in line with Xiao et al (2022); Ioannou et al (2023); Santos et al (2023), who confirmed that greenwashing decreases brand reputation. Third, the current research found that greenwashing harms brand credibility.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Second, this study addressed the fact that greenwashing has a detrimental impact on brand reputation. This result is in line with Xiao et al (2022); Ioannou et al (2023); Santos et al (2023), who confirmed that greenwashing decreases brand reputation. Third, the current research found that greenwashing harms brand credibility.…”
Section: Discussionsupporting
confidence: 87%
“…Xiao et al (2022) also confirmed that greenwashing decreases brand reputation and harms brand legitimacy. Moreover, Santos et al (2023) argued that greenwashing harms a company's reputation. Considering the discussions mentioned above, the following hypothesis is presented:…”
Section: Greenwashing and Brand Reputationmentioning
confidence: 99%
See 1 more Smart Citation
“…The global sustainable apparel market is valued at USD 11.2 million in 2023 and is projected to grow at a CAGR of 9.3% to reach USD 27.2 million by the end of 2033 (Fact.MR, 2022). However, there are many debates regarding whether the practices of these enterprises are involving the issue of greenwashing (Santos et al ., 2023) and whether these practices are in line with the principles of sustainable development (Izagirre-Olaizola, 2021). For example, fast fashion brands ZARA and HM have been promoting sustainable development in recent years and encouraging consumers to participate in “used clothes recycling” programs.…”
Section: Introductionmentioning
confidence: 99%